2004
DOI: 10.1074/jbc.m400070200
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal Domain Is the Primary Determinant of Histone H1 Binding to Chromatin in Vivo

Abstract: We have used a combination of kinetic measurements and targeted mutations to show that the C-terminal domain is required for high-affinity binding of histone H1 to chromatin, and phosphorylations can disrupt binding by affecting the secondary structure of the C terminus. By measuring the fluorescence recovery after photobleaching profiles of green fluorescent protein-histone H1 proteins in living cells, we find that the deletion of the N terminus only modestly reduces binding affinity. Deletion of the C termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
220
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(244 citation statements)
references
References 37 publications
19
220
1
2
Order By: Relevance
“…There can be at least two explanations for release of histone H1 from chromatin during mitosis; either a decreased H1 affinity for chromatin or an active exchange of H1 for other chromatin binding factors. Phosphorylation of H1, especially in its C terminal, is supposed to decrease its affinity for chromatin and increase its mobility in vivo (28) and, interestingly, recent experiments in vitro have shown that linker histones with fully phosphorylated C-terminal domains showed reduced affinity for DNA in combination with increased aggregation capacity of DNA fragments (29). In interphase cells, H1.2, H1.3, H1.4, and H1.5 are phosphorylated on serine residues (19,30).…”
Section: Discussionmentioning
confidence: 99%
“…There can be at least two explanations for release of histone H1 from chromatin during mitosis; either a decreased H1 affinity for chromatin or an active exchange of H1 for other chromatin binding factors. Phosphorylation of H1, especially in its C terminal, is supposed to decrease its affinity for chromatin and increase its mobility in vivo (28) and, interestingly, recent experiments in vitro have shown that linker histones with fully phosphorylated C-terminal domains showed reduced affinity for DNA in combination with increased aggregation capacity of DNA fragments (29). In interphase cells, H1.2, H1.3, H1.4, and H1.5 are phosphorylated on serine residues (19,30).…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence recovery after photobleaching (FRAP) experiments have demonstrated that the GD plays a dominant role in H1 binding to chromatin in cultured cells (14). FRAP experiments also indicate that the CTD plays an important role in the residence time of H1 in chromatin (15). In addition, experiments with oligonucleosome arrays assembled in vitro showed that the H1 CTD is required to condense the arrays into higher order structures (16 -18).…”
mentioning
confidence: 99%
“…38,39 Purified H1 from the human HeLa cells and H5 from chicken erythrocytes have been shown to inhibit ATP-dependent chromatin remodeling activities in vitro. 37,38 In the case of H5, inhibition of remodeling was abrogated by saturating phosphorylation of H5 using the cdc2 kinase. 41 Furthermore, using Xenopus extract model systems, only nonphosphorylated recombinant mammalian H1 represses chromatin remodeling during DNA replication and repair.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of CDK consensus S/T residues in mammalian H1s have been shown to alter mobility of H1 in chromatin, suggesting phosphorylation assists in release of H1 from chromatin. [35][36][37] Phosphorylation of the Tetrahymena H1 on S/T residues has been shown to influence transcriptional activity by creating an electrostatic charge patch that repels contact with DNA. 38,39 Purified H1 from the human HeLa cells and H5 from chicken erythrocytes have been shown to inhibit ATP-dependent chromatin remodeling activities in vitro.…”
Section: Discussionmentioning
confidence: 99%